A case of natural triploidy in European diploid green toad (Bufo viridis), with some distributional records of diploid and tetraploid toads - Borkin, L.J.; Shabanov, D.A.; Brandler, O.V.; Kukushkin, O.V.; Litvinchuk, S.N.; Mazepa, G.A.; Rosanov, J.M. (Russian Journal of Herpetology, 2007)
A triploid female (3n = 33) was found in diploid species Bufo viridis from the Crimea Peninsula, Ukraine. The case is recognized as an occasional autotriploidy. No morphological differences were found between this triploid female and other diploid specimens of the sample. Three categories of triploids in the Bufo viridis group are classified. Based on six green toad samples identified by chromosome number, the distribution of diploid and polyploid toads in Kazakhstan is discussed.
Keywords: Bufo viridis group; polyploidy; karyotype; the Crimea Peninsula